Commercialising smallholder agricultural production in Lao People's Democratic Republic. Issue 7 (3rd October 2017) - Alexander, Kim; Case, Peter; Jones, Michael; Connell, John
ABSTRACT: Many smallholder farmers in Lao People's Democratic Republic are transitioning from subsistence to commercial production. This article employs the Agriculture Innovation System (AIS) framework to report on empirical findings from six case studies of Lao smallholder production. It identifies the actors, organisations, and institutions involved in systemic commercialisation of subsistence farming and articulates patterns of interactions that contribute to the relative success of the transition. Of the factors identified in the case studies, the most important enablers of commercial production and adoption of innovative technologies were technical and financial assistance, access to markets, and the formation of farmer associations/organisations.